2016
DOI: 10.1007/s13197-016-2459-6
|View full text |Cite
|
Sign up to set email alerts
|

Serine protease inhibitors from squid ovary: extraction and its effect on proteolysis and gel properties of surimi

Abstract: Serine protease inhibitors from squid ovary (SOSPI) were extracted using different extraction media and conditions. Optimal condition included 0.45 M NaCl for 1 h. After heat treatment at 70°C for 10 min, the highest specific activity was obtained. Based on Sephadex G-75 gel filtration and activity staining, the major SOSPIs were present as monomer with molecular weight of 9.10 and 10.27 kDa. Impact of SOSPI on autolysis of bigeye snapper surimi was studied. Myosin heavy chain was more retained with coincident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…In WPC, an unidentified PI with an apparent MW of 101 kDa was detected and exhibited inhibitory action against papain and trypsin (Weerasinghe, Morrissey, Chung, & An, ). Recently, Singh and Benjakul () extracted and partially purified a serine PI from squid (Loligo formosana ) ovary.…”
Section: Pismentioning
confidence: 99%
See 3 more Smart Citations
“…In WPC, an unidentified PI with an apparent MW of 101 kDa was detected and exhibited inhibitory action against papain and trypsin (Weerasinghe, Morrissey, Chung, & An, ). Recently, Singh and Benjakul () extracted and partially purified a serine PI from squid (Loligo formosana ) ovary.…”
Section: Pismentioning
confidence: 99%
“…The total inhibitor activity and specific activity were increased by 58% and 62%, respectively, when the defatted roe was extracted using 10 mM phosphate buffer (pH 7) as the medium. Recently, a serine PI was retrieved from squid ovary using 0.45 M NaCl for 1 hr, and it exhibited the maximal specific inhibitory activity compared to the water extract (Singh & Benjakul, ). It has been demonstrated that chloride ions increase the solubility of PIs, by enhancing the electrostatic repulsion after binding to the positively‐charged groups of the protein (Singh & Benjakul, ).…”
Section: Extraction and Characterization Of Pismentioning
confidence: 99%
See 2 more Smart Citations
“…[21] Five cylindrical samples were cut into 2.5 cm height and 2.5 cm diameter and equilibrated at room temperature (25°C-28°C) before analyses. Sample was perpendicularly pressed by a spherical plunger of 5 mm diameter into the cut surface of gel at a constant depression speed (60 mm/min).…”
Section: Breaking Force and Deformationmentioning
confidence: 99%